Psychostimulants As Cognitive Enhancers in Adolescents: More Risk than Reward? - Urban, Kimberly R.; Gao, Wen-Jun (Frontiers in Public Health, 2017)
Methylphenidate and other psychostimulants, originally developed to treat attention deficit-hyperactivity disorder, are increasingly abused by healthy adolescents and adults seeking an advantage in scholastic performance and work productivity. However, how these drugs may affect cognitive performance, especially in the young brain, remains unclear. Here, we review recent literature and emphasize the risks of abuse of psychostimulants in healthy adolescents and young adults. We conclude that while the desire for cognitive enhancement, particularly with rising costs of education and increasingly competitive nature of scholarship programs, is unlikely to diminish in the near future, it is crucial for the scientific community to thoroughly examine the efficacy and safety of these stimulants in healthy populations across development. The current dearth of knowledge on the dose–response curve, metabolism, and cognitive outcomes in adolescents following methylphenidate or other psychostimulant exposure may be perpetuating a perception of these drugs as “safe” when that might not be true for developing brains.